PENERAPAN EVIDENCE BASED NURSING TERAPI DZIKIR TERHADAP PENINGKATAN KUALITAS HIDUP PADA PASIEN YANG MENJALANI HEMODIALISA DI RSPAD GATOT SOEBROTO - Erika Deliana (2023)
Hemodialysis is a replacement therapy for kidney function in patients with chronic kidney failure. There are still a number of problems related to the decrease in the quality of life of sufferers as a negative impact of hemodialysis therapy. An important issue as one of the effects of hemodialysis is spirituality. Good spirituality can support a person to have a good coping strategy. This research was conducted with the aim of improving the quality of life of hemodialysis patients with dhikr therapy intervention. This intervention was carried out on two patients undergoing hemodialysis at the Gatot Soebroto Army Hospital. Dhikr therapy is carried out for 15 minutes each time dhikr and its effectiveness is evaluated by filling out the Kidney Disease and Quality of Life Questionnaire (KDQOL-36). The evaluation results show that dhikr therapy can improve the quality of life of patients undergoing hemodialysis as evidenced by the significant increase in the KDQOL 36 questionnaire score.